Influence of cetyltrimethylammonium bromide on the morphology of AWO4 (A = Ca, Sr) prepared by cyclic microwave irradiation - Thongtem T. (2014)
AWO4 (A = Ca, Sr) was prepared from metal salts [Ca(NO3)2·4H2O or Sr(NO3)2], Na2WO4·2H2O and different moles of cetyltrimethylammonium bromide (CTAB) in water by cyclic microwave irradiation. The structure of AWO4 was characterized by X-ray diffraction (XRD) and selected area electron diffraction (SAED). Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) revealed the presence of nanoparticles in clusters with different morphologies; spheres, peaches with notches, dumb-bells and bundles, influenced by CTAB. Six Raman vibrational peaks of scheelite structure were detected at 908, 835, 793, 399, 332 and 210 cm-1 for CaWO4 and 917, 833, 795, 372, 336 and 192 cm-1 for SrWO4, which are assigned as ν1(Ag), ν3(Bg), ν3(Eg), ν4(Bg), ν2(Ag) and νf.r.(Ag), respectively. Fourier transform infrared (FTIR) spectra provided the evidence of W-O stretching vibration in [WO4]2- tetrahedrons at 793 cm-1 for CaWO4 and 807 cm-1 for SrWO4. The peaks of photoluminescence (PL) spectra were at 428-434 nm for CaWO4, and 447-451 nm for SrWO4. © 2008 Elsevier B.V. All rights reserved.